Prenylated Flavonoids in Topical Infections and Wound Healing - Sychrová, Alice; Škovranová, Gabriela; Čulenová, Marie; Bittner Fialová, Silvia (Molecules (Basel, Switzerland), 2022)
The review presents prenylated flavonoids as potential therapeutic agents for the treatment of topical skin infections and wounds, as they can restore the balance in the wound microenvironment. A thorough two-stage search of scientific papers published between 2000 and 2022 was conducted, with independent assessment of results by two reviewers. The main criteria were an MIC (minimum inhibitory concentration) of up to 32 µg/mL, a microdilution/macrodilution broth method according to CLSI (Clinical and Laboratory Standards Institute) or EUCAST (European Committee on Antimicrobial Susceptibility Testing), pathogens responsible for skin infections, and additional antioxidant, anti-inflammatory, and low cytotoxic effects. A total of 127 structurally diverse flavonoids showed promising antimicrobial activity against pathogens affecting wound healing, predominantly Staphylococcus aureus strains, but only artocarpin, diplacone, isobavachalcone, licochalcone A, sophoraflavanone G, and xanthohumol showed multiple activity, including antimicrobial, antioxidant, and anti-inflammatory along with low cytotoxicity important for wound healing. Although prenylated flavonoids appear to be promising in wound therapy of humans, and also animals, their activity was measured only in vitro and in vivo. Future studies are, therefore, needed to establish rational dosing according to MIC and MBC (minimum bactericidal concentration) values, test potential toxicity to human cells, measure healing kinetics, and consider formulation in smart drug release systems and/or delivery technologies to increase their bioavailability.
Keywords: nanotechnology; wound healing; Wound Healing; S. aureus; Anti-Bacterial Agents; mastitis; antiinfekční látky; Antioxidants; prenylated flavonoids; Anti-Infective Agents; Microbial Sensitivity Tests; hojení ran; antibacterial; cytotoxicity; flavonoidy; antioxidancia; Flavonoids; zvířata; Humans; MRSA; antibakteriální látky; mikrobiální testy citlivosti; skin; anti-inflammatory; antioxidant; lidé; Animals